Promoting language development in physically disabled adults through sports: The content and language integrated learning method - Bekirogulları, Hasan; Burgul, Nazım; Yagcı, Emete (Frontiers in Psychology, 2022)
This study reports on the outcomes of a qualitative study which explores the perceptions of ten wheelchair basketball players of the implementation of a CLIL program. The participants were all members of the official wheelchair basketball team of the Sports Federation for the Disabled in north Cyprus. They were all young adults (18-35 year olds) and their level of English language proficiency ranged from elementary to beginner. After a four-month CLIL intervention period, the data were elicited through individual interviews from the participants. A qualitative analysis of the textual data revealed the themes as improved self-image, high motivation, developed social skills and better speaking skills in the target language. The results have a few practical implications for English as a foreign language teachers, sports coaches and local disability committees.